Cobalt core-shell nanoparticles as precursors for cobalt-based Fischer-Tropsch synthesis catalysts - Govender, Alisa (Department of Chemical Engineering, 2019)
Core-shell nanoparticles may have an economic advantage over traditional nanoparticles as a catalyst, since the expensive, catalytically active material, which is subsurface, may be replaced with a cheaper counterpart. Furthermore, core-shell nanoparticles may be tailored to have a specific structure and composition at the nanoscale, due to a mixing of electronic properties of each phase and/or geometric effects. In this study, nickel ferrite (NiFe2O4) and zinc ferrite (ZnFe2O4) were chosen as core materials around which a cobalt (II, III) oxide (Co3O4) shell was grown. These ferrites were chosen due to their structural similarity to Co3O4 as this was expected to allow an epitaxial growth of the Co3O4 shell onto the ferrite core. Additionally, the difference in the lattice parameter between each ferrite core and the Co3O4 shell was postulated to introduce a varying degree of strain onto the shell, particularly after reduction when metallic cobalt should be present. Core-shell nanoparticles with either a nickel ferrite (NiFe2O4) core or a zinc ferrite (ZnFe2O4) core and a cobalt (II, III) oxide (Co3O4) shell (NiFe2O4@Co3O4 and ZnFe2O4@Co3O4 respectively) were synthesized, characterized and tested for their performance in the Fischer-Tropsch synthesis. These core-shell systems were compared to each other to evaluate the influence of the core and the applicability of NiFe2O4 or ZnFe2O4 as core nanoparticles in a cobalt-based Fischer-Tropsch catalyst. NiFe2O4@Co3O4 core-shell nanoparticles were also supported on Stöber silica spheres to determine the effect of the support on its properties and performance. The influence of two different reduction conditions, viz. 180°C (1 hour) or 230°C (2 hours), on the structure and Fischer-Tropsch synthesis performance of unsupported and Stöber silica spheres supported NiFe2O4@Co3O4 core-shell nanoparticles was also studied. Prior to the preparation of the core-shell nanoparticles, each ferrite core was prepared using the citrate precursor method. A Fe/M mole % ratio (where M is Ni or Zn) of 2.3 and calcination temperature of 450°C yielded phase pure NiFe2O4 or ZnFe2O4 nanoparticles with an average size of 14 nm. Using nickel ferrite (NiFe2O4) nanoparticles as a core, the growth of cobalt (II, III) oxide (Co3O4) around the core was studied by following a homogeneous precipitation synthesis. It was established that a two-step synthesis route was needed to synthesize the core-shell material with a fairly uniform Co3O4 shell. It was found that for both NiFe2O4@Co3O4 and ZnFe2O4@Co3O4 core-shell nanoparticles, the assynthesized materials had a Co3O4 shell around the ferrite core with an average thickness of 2 nm. NiFe2O4@Co3O4 and ZnFe2O4@Co3O4 core-shell nanoparticles were compared to each other as precursors for Fischer-Tropsch synthesis catalysts. Here, the first report on the nanoscale restructuring during reduction of these core-shell nanoparticles in pure hydrogen at 230°C and 250°C, respectively, was observed. This resulted in the formation of small cobalt islands on the ferrite surface. Catalytic testing of the core-shell materials, NiFe2O4@Co3O4 and ZnFe2O4@Co3O4, after reduction showed a cobalt-time yield of 13.64 µmolCO .gCo -1.s -1 and 4.27 µmolCO .gCo -1.s -1 and a C5+ selectivity of 47 C-% and 68 C-%, respectively. The observed difference in cobalt-time yield and selectivity between NiFe2O4@Co3O4 and ZnFe2O4@Co3O4 core-shell nanoparticles was due to a combination of effects that included the presence of cobalt islands over the surface of the core and the difference in extent of reduction of each core under Fischer-Tropsch synthesis conditions. The core-shell structure in NiFe2O4@Co3O4 core-shell nanoparticles was found to be retained with the use of mild reduction conditions of 180°C (1 hour). Thus, the performance in the Fischer-Tropsch synthesis of a system with a true core-shell structure with a cobalt shell was established. The former has not been reported to date. Owing to the former, strain effects may have contributed to NiFe2O4@Co3O4 core-shell (reduced at 180°C, 1 hour) having a low cobalt-time yield of 8.40 µmolCO .gCo -1.s -1 and a C5+ selectivity of 38 C-% during the Fischer-Tropsch synthesis. It was also shown that NiFe2O4@Co3O4 core-shell nanoparticles reduced at 180 °C (1 hour) had a similar activity to unsupported Co3O4, however, the former had a higher C5+ selectivity. The differences in the performance between NiFe2O4@Co3O4 core-shell (reduced at 180°C, 1 hour) and unsupported Co3O4 may have been due to strain effects. The nanoscale structural and compositional differences induced by each reduction condition applied may have been the cause for the inferior Fischer-Tropsch synthesis performance of these core-shell nanoparticles after reduction at 180°C for 1 hour than 230°C for 2 hours. The effect of a Stöber silica spheres support on the characteristics and Fischer-Tropsch synthesis behavior of NiFe2O4@Co3O4 core-shell nanoparticles was also investigated. Prior to characterization and the Fischer-Tropsch synthesis, NiFe2O4@Co3O4/SiO2 was reduced at either 180°C for 1 hour or 230°C for 2 hours. A higher cobalt-time yield (23.80 µmolCO .gCo -1.s -1) with a lower C5+ selectivity (44 C-%) was obtained with reduction at 230°C (2 hours) than 180°C (1 hour). After reduction at 230°C (2 hours), the influence of the support was clearly seen due to the higher activity obtained with NiFe2O4@Co3O4/SiO2. However, the unsupported and supported NiFe2O4@Co3O4 nanoparticles had similar product selectivities. After reduction at 230°C for 2 hours and exposure to Fischer-Tropsch synthesis conditions, the core-shell structure was retained in NiFe2O4@Co3O4/SiO2 possibly due to reducing the contact between the individual core-shell nanoparticles due to the presence of the support. This would be enhanced by anchoring the core-shell nanoparticles onto the Stöber silica spheres support.